The negotiated politics of social protection in sub-Saharan Africa - Sam Hickey; Tom Lavers; Miguel Ni\~no-Zarazúa; Jeremy Seekings (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Social assistance programmes proliferated and expanded across much of the global South from the mid-1990s. Within Africa there has been enormous variation in this trend: some governments expanded coverage dramatically while others resisted this. The existing literature on social assistance, or social protection more broadly, offers little in explanation of this variation. Drawing on the literature on political settlements and democratic politics, we argue that variation results from the political contestation and negotiation between political elites, voters, bureaucrats, and transnational actors. The forms of politics that matter at each of these inter-related sites of negotiation include struggles over ideas as well as material interests, and reflect the ways in which social assistance is being used to advance certain political as well as developmental projects in sub-Saharan Africa.
Keywords: H53; I38; N37; O55; 330; social assistance; politics; sub-Saharan Africa; international development organizations